The Integration of West Papuan Local Wisdom into Three-Dimensional Geometry: A Strategic Approach to Enhancing Students’ Learning Motivation - Wahyuni, Erik Tri; Parta, I Nengah; Purwanto, Purwanto (PRISMA, 2025)
This study aims to investigate the enhancement of students’ learning motivation and cognitive achievement through the implementation of a module-based instructional model integrated with the local wisdom of West Papua. Employing a quantitative descriptive approach with a one-group pretest–posttest design, data were collected using cognitive tests and a Likert-scale motivation questionnaire. Quantitative analysis was conducted using Minitab software to assess statistical significance, while students’ motivational responses were analyzed descriptively. The results revealed a substantial improvement in students’ cognitive performance, with the average score increasing from 40.80 (pretest) to 86.40 (posttest). A paired-sample t-test indicated a significant difference between pretest and posttest scores (t = -8.718, p < 0.05). Meanwhile, the motivation questionnaire results showed a significant enhancement in students’ learning motivation, with the mean Likert score rising from 3.2 (pretest) to 4.0 (posttest), corresponding to 100% positive responses categorized as highly valid. These findings demonstrate that integrating culturally responsive learning modules can effectively enhance both students’ cognitive understanding and their motivation toward learning mathematics. The local wisdom–based module has proven to be a feasible and engaging instructional tool for contextualized mathematics learning.